2007
DOI: 10.1111/j.1945-5100.2007.tb01072.x
|View full text |Cite
|
Sign up to set email alerts
|

In situ seismic measurements in borehole LB‐08A in the Bosumtwi impact structure, Ghana: Preliminary interpretation

Abstract: Abstract-In order to assist in the interpretation of previous seismic refraction and reflection surveys, a vertical seismic profile was acquired in the Lake Bosumtwi (Ghana) hard-rock core hole LB-08A. No seismic reflections are seen in the up-going wave field obtained, and this observation is consistent with the lack of reflectivity observed in the corresponding 2-D surface seismic profile obtained in earlier studies. Direct down-going P-waves were found both in the cased sediment column from a depth of 73 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Investigations performed in recent years at the Vorotilovo scientific deep well drilled in the Puchezh‐Katunk impact structure, Russia [ Popov et al , 1998], and at the Nördlingen‐1973 scientific well drilled in the Ries impact structure, Germany [ Popov et al , 2003a], demonstrated (1) low thermal anisotropy of rocks (brecciated, cataclased, thermally overprinted and shock transformed target rocks) and (2) low values of thermal conductivity, density and velocity in the rocks affected by the shock and postshock thermal conditions [ Schmitt et al , 2007] in comparison with similar rocks outside these impact structures.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations performed in recent years at the Vorotilovo scientific deep well drilled in the Puchezh‐Katunk impact structure, Russia [ Popov et al , 1998], and at the Nördlingen‐1973 scientific well drilled in the Ries impact structure, Germany [ Popov et al , 2003a], demonstrated (1) low thermal anisotropy of rocks (brecciated, cataclased, thermally overprinted and shock transformed target rocks) and (2) low values of thermal conductivity, density and velocity in the rocks affected by the shock and postshock thermal conditions [ Schmitt et al , 2007] in comparison with similar rocks outside these impact structures.…”
Section: Introductionmentioning
confidence: 99%
“…Lines labeled TI, TII, TIII, TIVb, and TV are paleolake surfaces discussed in the text. Velocities have been converted into depths as in the work by Schmitt et al [2006]. (b) Enlargement of seismic data showing truncation surfaces associated with estimated lake depths during TI and TII.…”
Section: Evidence For Paleolake Level Variationsmentioning
confidence: 99%
“…The recorded travel time and known depth level of the receivers provide the interval velocities necessary in deriving a time to depth relationship of the recorded seismic data. However, this is also restricted to the area between the seismic source and borehole location (Schmitt et al 2007). Seismic energy sources positioned within tens of meters of the borehole are considered to be a zero-offset VSP (Stewart 2001).…”
Section: Vertical Seismic Profilingmentioning
confidence: 99%
“…#1 and #3 correspond to the change in borehole diameter, whereas #2 corresponds to a known fracture zone that was previously interpreted from the geophysical logs penetration depth of a few centimeters in the borehole. Initial comparison of sonic log velocities to VSP velocities is difficult due to the frequency dispersion resulting from both rock property and scale-dependent effects (Sams et al 1997;Schmitt et al 2007). There is a significant amount of variation in VSP interval velocity as minor fluctuations of even the level of the digitization period of 1 ms in the first arrival pick could easily cause nonphysical variations in the velocities with the depth sampling interval of 2.5 m. This error is reduced using larger intervals in the velocity calculation at the cost of reduced resolution.…”
Section: Velocity Profilementioning
confidence: 99%
See 1 more Smart Citation